PLEASURE OF SPEECH IN THE LANGUAGE STYLE OF THE FRENCH YOUTUBER CYPRIEN - Alicia Nadine Cendekiaputri; Sajarwa Sajarwa; Aprillia Firmonasari (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Language as a part of the study of communication is often used to build individuals'